EFEKTIFITAS TERAPI TUINA CHUZHEN MEDITATIF, AKUPUNTUR DAN FOOD THERAPY TCM TERHADAP DIABETES GESTASIONAL - Hardi, Yelini Fan (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2022)
Background : Because a woman is susceptible to syndromes and symptoms that might result in abnormalities or freeclampsia throughout pregnancy, being pregnant is a very trying time for mothers. Diabetes in pregnant women is one of them. If this sickness is not addressed right away, it might damage many other organs, lead to severe disorders, and even result in premature birth. Objective: to evaluate the efficacy of acupuncture, TCM dietary therapy, and meditation tuina chuzhen therapy for gestational diabetes Method : Techniques that include interacting directly with patients or subjects for practice or demonstration result : provides a calming effect for people with gestational diabetes, aids in good digestion and regular bowel movements, strengthens the body's immune system, and regulates blood sugar levels Keywords : Gestational Diabetes, Akupuntur, Tuina Chuzhen, Traditional Chinese Medicine